Internal Migration and Socio-Economic Status of Migrants: A Study in Sylhet City, Bangladesh - Chowdhury, Iqbal Ahmed; Haque, Nadia; Kamal, Mohammad Mostufa; Islam, Tanjina; Khan, Mohammad Maniruzzaman; Islam, Mohammad Nazrul; Uddin, Imtiaz (American Journal of Human Ecology, 2012)
Migration is considered to be one of the important strategies for the progress and development of rural poor. People migrate from one place to another for the development of their overall living standard and to enhance their social position. This study tries to determine the factors of internal migration and assesses its impact on socio-economic status of migrants. Descriptive research design has been followed in this study. Social survey technique and Focused Group Discussion (FGD) have been applied to collect pertinent data. To analyze the collected data Economic Status Index (ESI), Social Status Index (SSI), Head Count Ratio (HCR) and Poverty Gap Ratio (PGR) were calculated. Area under Sylhet City Corporation, Bangladesh, where people have been migrating from different district of Bangladesh, has been considered as the area of this study. The study reveals that, people were pushed in Sylhet city because of their poor socio-economic conditions, mainly poverty condition. Besides, many pull factors also attract them to migrate in this city. It is found from the study that, internal migration is positively contributed to the development of poor people. There social and economic condition as household income, saving, land possession, expenditure, non-productive assets, housing status, water & sanitation facilities, treatment aptitudes, social participation etc. especially their poverty condition is improved in comparison to the same factors before migration. In a word, internal migration (rural to urban) contributes to the improvement of the socio-economic status of the migrants.